2016
DOI: 10.1182/blood-2016-01-628982
|View full text |Cite
|
Sign up to set email alerts
|

T cells for viral infections after allogeneic hematopoietic stem cell transplant

Abstract: Despite recent advances in the field of allogeneic hematopoietic stem cell transplantation (HSCT), viral infections are still a major complication during the period of immune suppression that follows the procedure. Adoptive transfer of donorderived virus-specific cytotoxic T cells (VSTs) is a strategy to rapidly restore virus-specific immunity to prevent or treat viral diseases after HSCT. Early proof of principle studies demonstrated that the administration of donor-derived T cells specific for cytomegaloviru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
155
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 191 publications
(164 citation statements)
references
References 85 publications
2
155
0
7
Order By: Relevance
“…In addition, the strategy is HLA restricted and targeting a single viral epitope increases the risk of viral immune escape. However, a clinical trial is currently underway in the United Kingdom evaluating T cells transduced with a retroviral vector expressing a CMVspecific TCR for high-risk patients after HSCT (Morris et al) (97).…”
Section: Tcr-gene Modificationmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the strategy is HLA restricted and targeting a single viral epitope increases the risk of viral immune escape. However, a clinical trial is currently underway in the United Kingdom evaluating T cells transduced with a retroviral vector expressing a CMVspecific TCR for high-risk patients after HSCT (Morris et al) (97).…”
Section: Tcr-gene Modificationmentioning
confidence: 99%
“…These T cells suppressed viral replication compared with unexpanded CD8 T cells, and CMV and EBV-specific T cells derived from the same HIV-seronegative donors. This holds promise in the CB setting and HIV-specific T cells manufactured this way are currently studies utilizing donor-derived HIV-specific T cells after allogeneic HSCT are being planned (97). Moreover, the group at Children's National is currently exploring the potential expanding HIV-specific T cells from CB using a non-HLA restricted GMP compliant approach (101).…”
Section: Hiv-specific T Cellsmentioning
confidence: 99%
“…Potential limitations include the need for additional donor leukapheresis to collect sufficient starting material, which can be burdensome, particularly in the unrelated donor setting. Additionally, this method has a requirement for circulating VSTs, and is therefore not available to virus-naive donors or CMV-seropositive donors who do not respond to pp65 or IE-1 stimulation (57).…”
Section: R E V I E W S E R I E S : T R a N S P L A N Tat I O Nmentioning
confidence: 99%
“…In the post-HSCT setting, gross impairment of T cell function liberates EBV-infected B cells (usually donorderived) to outgrow, causing post-transplant lymphoproliferative disorder (PTLD). PTLD risk is particularly high in patients receiving enhanced immune suppression for the treatment of GVHD, and in those receiving anti-thymocyte globulin (57,67).…”
Section: Ebv: Biology and Pathogenicity In The Post-hsct Settingmentioning
confidence: 99%
“…(Taylor et al 2015) The most immunogenic of these is post-transplant lymphoproliferative disease and many studies have shown that infusions of EBV-specific T-cells derived from an EBV seropositive normal HSCT donor can induce complete remission in over 70% of patients who develop this complication after HSCT. (Bollard and Heslop 2016, Doubrovina et al 2012, Heslop et al 2010) Initial manufacturing strategies for donor-derived EBV-specific T-cells were lengthy, because they used lymphoblastoid cell lines (LCLs) as a source of EBV antigen. With the availability of overlapping peptide libraries spanning individual EBV antigens, several groups have shortened the process and shown that rapidly expanded EBV-specific T-cells induce similar response rates.…”
Section: Targeting Tumour-associated Antigens With Native T-cell Recementioning
confidence: 99%